Ответы и объяснения

Лучший Ответ!
2012-01-09T08:38:09+00:00

y^2 + y = 0

y1 = -1; y2 = 0 

y^{-}(x) = C1*e^{-1*x} + C2*e^{0*x}  

y^{-}(x) = C1*e^{-x} + C2 

 

y_{*}(x) =(A*cos(5x)+B*sin(5x))*e^{0*x}*x^{0} 

y_{*}(x) =A*cos(5x)+B*sin(5x) 

y_{*}^{'}(x) =-5*A*sin(5x)+5*B*cos(5x) 

y_{*}^{''}(x)=-25*A*cos(5x)-25*B*sin(5x) 

 подставляем в уравнение и находим коэффициенты

-25*A*cos(5x)-25*B*sin(5x)+A*cos(5x)+B*sin(5x)=2*cos(5x)+3*sin(5x) 

cos(5x): A-25*A=2=> A=-\frac{1}{12} 

sin(5x): B-25*B=3=> B=-\frac{1}{8}

 

y(x) =y_{*}(x)+y^{-}(x) 

y(x) =-\frac{1}{12}*cos(5x)-\frac{1}{8}*sin(5x)+C1*e^{-x}+C2